A Comprehensive Parametric Analysis of Vertical Handoff using Ant Colony Optimization - Sivvam, Sandeep; Neeraja, S.; Dharma Raj, C. (International Journal of Engineering and Technology, 2018)
With the development of 4G mobile telecommunication systems, providing users with the convenience of a seamless continuous connection is not enough anymore. With best Quality of Service (QoS) users want to be connected to the best available network. Hence, it is necessary to have good decision making algorithm that will decide whether to perform handoff to another network, the best network to vertically perform handoff to, and the right time to initiate the handover. The key aspects leading to deployment of extensive array of wireless and mobile networks are advances in miniaturization, circuit design with low power and development in radio access technologies and demand for high speed internet access increase in user. The choice of parameters plays significant role in the decision of vertical handoff. Parameters like power consumption, bandwidth, velocity, signal strength, cost, throughput, user preferences and load falling on network are considered during vertical handoff. Optimization helps in using these available resources in best possible manner as in many cases vertical handoff takes place in situations where the resources are very limited. In this paper only the parameter Power is taken into consideration and Ant colony optimization technique is applied and the comparison for power before and after optimization is plotted.Â Â Â